The antivirus hacker's handbook - Koret, Joxean; Bachaalany, Elias (John Wiley & Sons, Inc., 2015)
The Antivirus Hacker's handbook shows you how to hack your own system's defenses to discover its weaknesses, so you can apply the appropriate extra protections to keep you network locked up tight."--Back cover